Lean mass asymmetry is weakly associated with jumping performance in NCAA Division I basketball players - Bailey, C.; Eusufzai, R.; Wright, A. (The Journal of Strength and Conditioning Research, 2021)
Asymmetry measurement in sport performance has been popular in recent research. Studies have demonstrated a potential link to performance decrements in vertical jumping with increasing force production asymmetry. To the current authors' knowledge, only one study has investigated the influence lean mass asymmetry has on jumping performance and found performance decrements, but lean mass asymmetry only accounted for a small portion of the variance in jumping performance. Purpose: The purpose of this study was to evaluate the association between lean mass asymmetry and jumping performance in NCAA Division I basketball players. Methods: 12 male NCAA Division I basketball players volunteered for this study (age = 21.8 ± 1.2 years, height = 1.9 ± 0.1 m, body mass = 85.9 ± 9.1 kg). Athletes completed body composition assessment via dual energy x-ray absorptiometry (GE Lunar iDXA) to reveal segmental lean mass data for each side of the lower body (LB) and total body (TB). Countermovement jump (CMJ) assessment was completed in the same session on a force plate (AMTI, ACP) collecting data at 1,000 Hz to produce data for jump height (JH), peak power (PP), and propulsive impulse (Imp). Asymmetry magnitudes were quantified with the Limb Symmetry Index (LSI) {(larger value - smaller value)/(1/2[sum of values]) ×100} or TB SI ((larger value—smaller value)/((sum of values)), representing asymmetry as a percentage. Association between lean mass asymmetry and CMJ performance variables were evaluated with Pearson's product-moment correlations or Spearman's rank correlations depending on data normality. Results: LB LSI data were normally distributed, while TB LSI data were not (Shapiro-Wilk p = 0.839 & p = 0.009 respectively). Associations are shown as scatter plots in Figure 1. Pearson's correlations revealed only trivial to small negative relationships between LB LSI and JH (r = -0.103), PP (r = -0.312), and Imp (r = -0.258). A Spearman's correlation coefficient revealed a similar trend with TB SI (r = -0.302). No correlations resulted in statistical significance. Conclusions: These results are somewhat consistent with the only other study examining lean mass asymmetry and jumping performance decrement (Bell et al., 2014), in that lean mass asymmetry does not fully explain the interaction between force production asymmetries and overall jumping performance. Specifically, data from the current investigation suggests that it can only explain a trivial amount of the variance (<10%). Additional aspects, such as neuromuscular control and strength, need to be considered to fully understand this interaction. Practical Application: Lean mass asymmetry should not be considered the primary cause of poor jumping performance or force production asymmetry. It is likely that variables such as neuromuscular control and strength play a much larger role in explaining force production and jumping performance.